Matched and mismatched unrelated donor compared to autologous stem cell transplantation for acute myeloid leukemia in first complete remission: a retrospective, propensity score-weighted analysis from the ALWP of the EBMT. Issue 1 (December 2016) - Saraceni, Francesco; Labopin, Myriam; Gorin, Norbert-Claude; Blaise, Didier; Tabrizi, Reza; Volin, Liisa; Cornelissen, Jan; Cahn, Jean-Yves; Chevallier, Patrice; Craddock, Charles; Wu, Depei; Huynh, Anne; et al.
Abstract Background Optimal post-remission strategy for patients with acute myeloid leukemia (AML) is matter of intense debate. Recent reports have shown stronger anti-leukemic activity but similar survival for allogeneic stem cell transplantation (allo-HSCT) from matched sibling donor compared to autologous transplantation (auto-HSCT); however, there is scarcity of literature confronting auto-HSCT with allo-HSCT from unrelated donor (UD-HSCT), especially mismatched UD-HSCT. Methods We retrospectively compared outcome of allogeneic transplantation from matched (10/10 UD-HSCT) or mismatched at a single HLA-locus unrelated donor (9/10 UD-HSCT) to autologous transplantation in patients with AML in first complete remission (CR1). A total of 2879 patients were included; 1202 patients received auto-HSCT, 1302 10/10 UD-HSCT, and 375 9/10 UD-HSCT. A propensity score-weighted analysis was conducted to control for disease risk imbalances between the groups. Results Matched 10/10 UD-HSCT was associated with the best leukemia-free survival (10/10 UD-HSCT vs auto-HSCT: HR 0.7, p  = 0.0016). Leukemia-free survival was not statistically different between auto-HSCT and 9/10 UD-HSCT (9/10 UD-HSCT vs auto-HSCT: HR 0.8, p  = 0.2). Overall survival was similar across the groups (10/10 UD-HSCT vs auto-HSCT: HR 0.98, p  = 0.84; 9/10 UD-HSCT vs auto-HSCT: HR 1.1, p  = 0.49). Notably, in intermediate-risk patients, OS was significantly worse for 9/10 UD-HSCT (9/10 UD-HSCT vs auto-HSCT: HR 1.6, p  = 0.049), while it did not differ between auto-HSCT and 10/10 UD-HSCT (HR 0.95, p  = 0.88). In favorable risk patients, auto-HSCT resulted in 3-year LFS and OS rates of 59 and 78 %, respectively. Conclusions Our findings suggest that in AML patients in CR1 lacking an HLA-matched sibling donor, 10/10 UD-HSCT significantly improves LFS, but this advantage does not translate in better OS compared to auto-HSCT. In intermediate-risk patients lacking a fully HLA-matched donor, auto-HSCT should be considered as a valid option, as better survival appears to be provided by auto-HSCT compared to mismatched UD-HSCT. Finally, auto-HSCT provided an encouraging outcome in patients with favorable risk AML.